The Academic Writing Needs of Students: A Case Study on Stakeholder Perspectives - Sağlamel, Hasan; Aydoğdu, Zeynep Merve (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
The international appeal of English has resulted in an expansion of courses adopting English-medium instruction, and many institutions require students to pursue their studies in programs with English medium. However, to what extent these programs meet the expectations is yet to be understood. Numerous studies have documented the effectiveness of EMI particularly in English as a foreign language contexts. However, perspectives of different stakeholders were not adequately captured. The present study attempts to fill this void by exploring students' needs of academic writing from the perspectives of different stakeholders. A total of 9 participants, namely, 5 students, a language instructor, and 3 teachers of content professors were selected using the snowball sampling method. All the participants were selected from a department offering English-medium instruction at a state university in Turkey. Data were collected through semi-structured interviews. The results show that students require more investment in academic writing courses to get familiar with the disciplinary register and fulfil the requirements of future English courses. The stakeholders’ perspectives are compared to have a better understanding of students’ needs, lacks and wants. The study suggests some implications to approach language education policies more critically.